Environmental impact minimization of reticular structures made of reused and new elements through Life Cycle Assessment and Mixed-Integer Linear Programming - Brütting, Jan; Vandervaeren, Camille; Senatore, Gennaro; De Temmerman, Niels; Fivet, Corentin (Energy and buildings, 2020)
•Structural optimization with integrated Life Cycle Assessment.•Globally optimal element assignments via mixed-integer linear programming.•Environmental impact reduction by up to 56% for structures made of reused elements.•Statistical analysis carried out through varying 100 stock configurations.•Combining reused and new elements results in least environmental impact structures. An important share of building environmental impacts is embodied in load-bearing structures because of their large material mass and energy-intensive fabrication process. To reduce substantially material consumption and waste caused by the construction industry, structures can be designed and built with reused elements. Structural element reuse involves: element sourcing and deconstruction, reconditioning and transport. As these processes also generate environmental impacts, reuse might not always be preferred over new construction. This paper presents a method to design reticular structures with minimal environmental impact made from reused and new elements. The formulation given in this paper is based on a combination of Life Cycle Assessment (LCA) and discrete structural optimization. The LCA carried out in this work accounts for impacts generated from sourcing reclaimed elements to the assembly of the structure. Structural optimization is subject to stress constraints on element capacity and deflection limits for serviceability. Typical loading scenarios are considered. The method is applied to the design of three single-span steel trusses of different topology subject to 100 simulated stocks of reusable elements that have varying cross-sections and lengths. Benchmarks against minimum-weight solutions made solely from recycled steel show that this method produces structures with up to 56% lower environmental impact. Depending on stock availability, the lowest environmental impact is achieved through a combination of reused and new elements.